PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN OTOMOTIF (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 SAMPAI 2019) - Siti Nurlatifah, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this study is to determine the effect of The Capital Structure, Profitability and Dividend Policy on Firm Value. The research method is carried out by first determining the object of research, population and sample as well as data collection techniques. In this research, the type used is secondary data The research method is to use quantitative analysis which analyzes the description of the data through the data by means of the minimum, maximum, average and standard deviation of each variable under study. . This study uses simple regression analysis techniques and multiple regression and uses SPSS 25 program analysis tools. From the results of the research that has been done, it is found that the Capital Structure, Profitability and Dividend Policy have a simultaneous and partial effect on the Value of Automotive Companies Listed on the Indonesia Stock Exchange for the Period 2017 to 2019